Cerebral Angiography Normal Anatomy and Vascular Pathology - Bradac, Gianni Boris; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This revised and enlarged edition of Cerebral Angiography, which includes new angiographic studies and illustrative drawings, offers detailed guidance on diagnostic use of the procedure. The first part of the book describes the normal anatomy of the cerebral arteries and veins, with attention to morphological aspect, embryological development, function, and vascular territories. The intraorbital and extracranial vascularization is also considered. The reader will gain a sound knowledge of normal vascular anatomy and its variations that will serve as a basis for the correct interpretation of pathological processes and their clinical significance, as covered in the second part of the book. Among the pathologies considered are vascular abnormalities, including angiomas, fistulas and aneurysms; atherosclerotic and non-atherosclerotic stenosis and occlusion of the cerebral vessels; venous thrombosis; intraorbital and extracranial vascular malformations. Pathogenesis, morphological and dynamic aspects, responsible for clinical symptoms and influencing the therapy are described. While the emphasis throughout is on the diagnostic value of cerebral angiography, many examples of endovascular treatment in different pathological situations are also presented, with discussion of indications, risks and results.
Aortic Arch and Origin of the Cranial Cerebral Arteries -- Carotid Artery -- External Carotid Artery -- Anterior Cerebral Artery -- Middle Cerebral Artery -- Extra- and Intracranial Vertebrobasilar Sector -- Posterior Cerebral Artery -- Vascular Territories -- Cerebral Veins -- Extracranial Venous Drainage -- Aneurysms -- Vascular Malformations of the Central Nervous System -- Dural Arteriovenous Fistulas -- Arteriovenous Fistulas -- Atherosclerosis -- Spontaneous Dissection of Carotid and Vertebral Arteries -- Other Non atherosclerotic Vasculopathies -- Cardiac Diseases -- Arterial Occlusive Diseases in Children -- Cerebral Venous Thrombosis.
Keywords: Neuroradiology; Neurology .; Neurosurgery; Otorhinolaryngology; Oral surgery; Maxillofacial surgery; Vascular surgery; Neuroradiology; Neurology; Neurosurgery; Otorhinolaryngology; Oral and Maxillofacial Surgery; Vascular Surgery